2011
DOI: 10.4028/www.scientific.net/kem.471-472.686
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and Flexural Behavior of Hybrid Banana Pseudostem/Glass Fibre Reinforced Polyester Composites

Abstract: Natural fibre-based thermoset composites are generally lower in strength performance compared to synthetic thermoset composites. Hybridization with some amount of synthetic fibre enhanced the mechanical properties of the composites. This study focused on the performance of mechanical properties of hybrid banana/glass fibre reinforced polyester composites. Hybrid composites with different volume ratios of banana to glass fibre were prepared. The reinforcing effect of both fibres in polyester is also evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The use of polysaccharide-like cellulose as natural filler in various polymer composite systems has been widely investigated by many researchers [1][2][3][4]. This is due to the fact that the cellulose is one of the most abundant polymers on the earth, which is also low-cost, non-toxic, renewable, environmentally friendly and biodegradable [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The use of polysaccharide-like cellulose as natural filler in various polymer composite systems has been widely investigated by many researchers [1][2][3][4]. This is due to the fact that the cellulose is one of the most abundant polymers on the earth, which is also low-cost, non-toxic, renewable, environmentally friendly and biodegradable [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…20 The flax/glass hybrid composites based on continuous reinforcement showed good tensile and flexural properties as compared to flax composite. 21 In another study, Hanifawati et al 22 evaluated the tensile and flexural strengths of banana/ glass hybrid composites and results indicated that the incorporation of small fraction of glass fibres in banana-polymer composite show enhancement in tensile and flexural properties.…”
Section: Introductionmentioning
confidence: 99%
“…The tensile strength is greatly dependent on effective and uniform stress distribution [53]. In the present study, the increased strength of the interwoven hybrid composite was primarily attributed to the high strength of the hemp fibre rather than the low strength of the PET fibre [54]. This is indicated by the strength properties shown in Table 1; the strength of the hemp fibre (250 MPa) was double that of the PET fibre (100 MPa).…”
Section: Tensile Propertiesmentioning
confidence: 47%